IMPLEMENTASI KEBIJAKAN PENERTIBAN KELOMPOK PENGGANGGU FUNGSI JALAN DI KOTA PEKANBARU - Milani Novriani; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
One of the traffic problems in Pekanbaru City is a congestion caused by a buildup of vehicles which causes traffic flow to become obstructed and even stop. The existence of traffic police who are not always there to control the road from congestion has led to the emergence of a group that disrupts the function of the road or commonly called “Pak Ogah” who takes over the role of the Police. "Pak Ogah" is someone who controls the road at a crossroads or a U-turn with the intention of expecting a reward in the form of money from passing drivers. The existence of "Pak Ogah" raises pros and cons among the people of Pekanbaru City. There are those of the view that the existence of "Pak Ogah" is quite helpful in regulating traffic and making it easier for cars that want to turn / turn around, especially during heavy and congested traffic. Meanwhile, some people argue that the existence of "Pak Ogah" can exacerbate traffic jams and disturb car drivers. So the Pekanbaru City Traffic Police and Pekanbaru City Satpol PP held raids to curb the "Pak Ogah". The purpose of this study is to determine how the implementation of policing policies for road function disturbing groups in Pekanbaru City and to find out what are the factors that hinder the implementation of policing policies for road function disturbing groups in Pekanbaru City. This study used purposive sampling technique with qualitative research using a descriptive approach and the required data, both primary and secondary data, were obtained through observation, interviews and documentation and then analyzed based on the research problem. The results of this study indicate that the implementation of policing policies for road disruptive groups in Pekanbaru City has not been going well. The factors that hinder the control of groups that interfere with the function of the road, namely the target group who escaped when it was curbed, the application of weak sanctions, and the motorists who gave money to the groups that disturbed the function of the road.Keywords: Implementation, Public Policy, discipline Pak Ogah